MENAKAR HASIL PELATIHAN DASAR CALON PEGAWAI NEGERI SIPIL DI BALAI DIKLAT KEAGAMAAN BANDUNG DENGAN EVALUASI KIRKPATRICK - Dedi Restendi; Ranti Nuranita (Balai Diklat Keagamaan Banjarmasin, 2021)
Basic training for prospective civil servants is the starting point for efforts to create civil servants who have basic knowledge of the government administration system, have a national perspective, have personality and ethics. Balai Diklat Keagamaan Bandung as a government institution in the field of training has the responsibility for the success of creating a civil servant figure who has followed the latsar as the final result, the Kirkpatricks level IV evaluation is the result, able to measure the extent to which the ability to develop work patterns, contribution to organization and speed and accuracy in the work of a civil servant who has followed latsar.